The Urgency of Female Peacekeepers’ Involvement in Addressing Gender-Based Violence in Palestine - Az-Zahra Shahnaz, Balqish; Harisman, Harisman (Journal of Law, Politic and Humanities, 2024)
The UN Peace Mission is a tool established by the UN to provide assistance and political support and facilitate peacebuilding for countries that are in conflict or are in transition from conflict to peace. Palestine is one of the regions in the Middle East and North Africa, where in this region there is inequality between men and women that still persists and is supported by patriarchy. Women and girls in Palestine continue to experience various forms of violence due to patriarchal norms and culture that are rooted in their society. This research will discuss the importance of gender equality issues in the international sphere, especially gender violence that occurs in Palestine, besides that this research will discuss the Importance of the Involvement of Women Peacekeepers in Overcoming Gender-Based Violence in Palestine, the discussion in this study includes the Urgency and impact of the Involvement of Women Peacekeepers on Gender-Based Violence in Palestine. Based on the results of the study, it shows that the involvement of female peacekeepers in the prevention of gender-based violence in Palestine can be a stimulus for other countries to participate in helping and reducing the number of gender-based violence, besides seeing that gender-based violence in Palestine is an urgent matter to be resolved, the involvement of Indonesian peacekeepers in the prevention of gender-based violence in Palestine will provide a new fighting direction for Palestine and other countries in conflict.